The Effect of Competency and Work Discipline on Employee Performance at PT Geo Dipa Energi Persero - Sefnie Chabita Wardhanie; Cecep Haryoto (MES Management Journal, 2025)
This study examines the effects of competence and work discipline on employee performance at PT Geo Dipa Energi (Persero) using a quantitative associative approach. Primary data were collected through structured questionnaires distributed to 60 employees as research respondents, and the data were analyzed using multiple linear regression with the assistance of SPSS software. The findings reveal that competence has a positive and significant effect on employee performance, as indicated by a t-value of 4.565 with a significance level below 0.05, suggesting that employees’ knowledge, skills, and abilities play an important role in improving performance outcomes. In addition, work discipline also shows a positive and significant influence on employee performance, evidenced by a t-value of 4.567 and a significance level below 0.05, which indicates that adherence to organizational rules, punctuality, and responsibility contribute to higher levels of performance. Simultaneously, competence and work discipline have a significant effect on employee performance, as demonstrated by an F-value of 40.821, which exceeds the F-table value of 3.16 with a significance level below 0.05. These results confirm that employee performance at PT Geo Dipa Energi (Persero) is strongly influenced by both individual competence and disciplined work behavior, implying that management should focus on enhancing employee competencies and strengthening work discipline to achieve optimal organizational performance.